STRATEGI PENGELOLAAN MUSEUM ASI MBOJO SEBAGAI DAYA TARIK WISATA BUDAYA DI KABUPATEN BIMA – NTB - Wahyuni, Indri (Humanis; Volume 1. No. 2. Desember 2012)
Museum represent a functioning institute as medium of education, information cebter, source of science, and also as fascination of wisata. Important seeing of function him of museum hence writer interest to lift and potency and management of Asi Mbojo Museum as fascination of wisata in area of Bima – NTB. Starting from lifted problems the mentioned that is potency of museum management and Asi Mbojo exist in Asi Mbojo Museum. To reach the target, hence determined by program plan management of Asi Mbojo Museum as formulated cultural wisata object as follows : correcting organization chart of Asi Mbojo Museum, settlement of showroom remain to, provide fund in conservacy, doing conduction collection labelisasi, braiding job/activity or communications is equal to party/side or related/relevant instution, forming security guard and hygiene, adding the amount of officers comprehending concerning officer, doing/conducting activity of promotion, making brochure and guidebook, renovating damage facility or building, levying of areal park, conservancy of facility of toilett, levying of artshop-artshop and canteen.
Keywords: Museum Asi Mbojo, Strategy Management, collection.